Why is “not infrequent” not always “frequent”? Double negation in political discourse - Osmankadić, Merima (ExELL, 2025)
The aim of this paper is to view double negation in the light of its semantic and pragmatic meaning. While double negation in logic gives a positive value, in natural languages, besides having positive entailment, it can have a range of different implicatures and functions. Thus, depending on different discoursal factors, double negation can be used for different motives, e.g. the speaker is not sure whether a certain proposition is true or is sure that it is not true, to name just one. The analysis is carried out on the database consisting of the reports, interviews and articles of the High Representative and his associates in Bosnia and Herzegovina in the period from 1995 to 2001.